2000
DOI: 10.1242/dev.127.8.1607
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the mammalian cardiac neural crest

Abstract: A subpopulation of neural crest termed the cardiac neural crest is required in avian embryos to initiate reorganization of the outflow tract of the developing cardiovascular system. In mammalian embryos, it has not been previously experimentally possible to study the long-term fate of this population, although there is strong inference that a similar population exists and is perturbed in a number of genetic and teratogenic contexts. We have employed a two-component genetic system based on Cre/lox recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,031 publications
(114 citation statements)
references
References 35 publications
5
109
0
Order By: Relevance
“…In addition to ablation models, lineage tracing, which identifies and tracks cell populations in vivo, provides an advanced way to uncover NC-derived cardiovascular contributions. Ablation and lineage tracing experiments have shown that cardiac NCCs in amniotes originate between the optic vessel and third somite, and migrate to pharyngeal arches three, four and six, to contribute to smooth muscle development, septation of the OFT, and patterning of the septa, valves, and aortic arch arteries [7,40,41]. Recently, Tang and colleagues, using retroviral labeling in chicks and Wnt1-Cre reporter lines in mice, found that a portion of NCCs also contributes to ventricle trabecular myocardium, however, further and more in-depth lineage mapping of cardiac NCCs is needed to confirm these conclusions [42].…”
Section: Contributions Of the Cardiac Neural Crest To Cardiac Formationmentioning
confidence: 99%
“…In addition to ablation models, lineage tracing, which identifies and tracks cell populations in vivo, provides an advanced way to uncover NC-derived cardiovascular contributions. Ablation and lineage tracing experiments have shown that cardiac NCCs in amniotes originate between the optic vessel and third somite, and migrate to pharyngeal arches three, four and six, to contribute to smooth muscle development, septation of the OFT, and patterning of the septa, valves, and aortic arch arteries [7,40,41]. Recently, Tang and colleagues, using retroviral labeling in chicks and Wnt1-Cre reporter lines in mice, found that a portion of NCCs also contributes to ventricle trabecular myocardium, however, further and more in-depth lineage mapping of cardiac NCCs is needed to confirm these conclusions [42].…”
Section: Contributions Of the Cardiac Neural Crest To Cardiac Formationmentioning
confidence: 99%
“…Mesenchymal cells of neural crest origin (cardiac neural crest, CNC) migrate from the hindbrain into the distal OFT and populate the endocardial cushions beginning at approximately E9.5. As OFT remodeling progresses, CNC cells proliferate, condense, and migrate proximally toward the right ventricle [18][19][20]. OFT cushions in the proximal region are also composed of mesenchymal cells that arise from an endocardial to mesenchymal transformation (EndoMT).…”
Section: Development Of the Aortic Valvementioning
confidence: 99%
“…By approximately E11.5, the major OFT cushions join and fuse at the midline; this fusion separates the common OFT into the separate pulmonary and aortic channels (P and A in Figure 1A,B,B',C'). As the AoV and PV are formed and sculpted throughout OFT remodeling, a subset of myocardial cells [26], as well as a portion of CNC cells, differentiate into smooth muscle cells (SMCs) and contribute to the aortic root and ascending aortic wall, respectively [20,27]. However, in spite of the developmental interdependence of the aortic valve and ascending aorta, few genes have been discovered that, when disrupted, give rise to both BAV and ascending aortopathies [28].…”
Section: Development Of the Aortic Valvementioning
confidence: 99%
“…Originated as ectodermal cells at the border of the neural plate at the dorsal neural tube, NCCs undergo epithelial to mesenchymal transition (EMT), then migrate to the ventral destinations. Lineage tracing studies demonstrate that NCCs give rise to a broad range of cell types in craniofacial and cardiovascular tissues (Chai et al, 2000;Jiang et al, 2000Jiang et al, , 2002Yoshida et al, 2008). NCCs derivatives are also identified in the developing midbrain (Jiang et al, 2002;Lewis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%